Untranslatability Found in J.K. Rowling’s English Novel Harry Potter and The Sorcerer’s Stone and Its Uzbek Version - Ruzmatova Nigora Nodir qizi; I. A. Jurayeva (Zien Journals, 2023)
The untranslatability issue in J.K. Rowling's work Harry Potter and the Sorcerer's Stone is the subject of this study. The goal is to identify the several categories of untranslatability, their root causes, and the translator's approach to resolving them in this work. Using 27 pieces of data, the researcher identifies two categories of untranslatability in J.K. Rowling's Harry Potter and the Sorcerer's Stone: linguistic and cultural. The novel also contains nine reasons why it cannot be translated. The semantically complicated words or phrases that are distinctive to a culture are the main reason. As a result of the investigation, it was shown that translators frequently utilize the borrowed word or the loan word with explanation technique to tackle the issue of untranslatability in this novel.
Keywords: Untranslatability; Linguistic Untranslatability; Cultural Untranslatability; whisperers